Evaluation of productive performance of broiler in response to Koroch (Pongamia pinnata) cake feeding - Habib, Masuma; Ferdaus, Abu Jafur Md; Islam, Md Touhidul; Hassin, Begum Mansura; Ali, Md Shawkat (Research in Agriculture Livestock and Fisheries, 2016)
The study was conducted for a period of 28 days to investigate the response of broiler to the inclusion of de-oiled koroch (Pongamia Pinnata) seed cake in the diet of broiler. A total of 192 day-old broiler chicks were individually weighed and randomly allocated to 4 dietary treatment groups having 4 replications of 12 chicks each, in a completely randomized design. Broilers under treatment 1 received a basal diet containing no koroch seed cake, considered as control; in treatment 2, 3 and 4, broilers were fed on basal diet containing 2%, 4% and 6% koroch seed cake, respectively. All productive performances (live weight, live weight gain, feed consumption and feed efficiency) of broiler fed on koroch seed cake were significantly (P<0.01) depressed compared to the control. The degree of depression was increased with the increasing level of koroch seed cake in the diet at all ages of broiler. The meat yield parameters showed a non-significant (P>0.05) effect except for the percentage of dressing yield, breast, liver and gizzard weight for the broilers in all treatment groups. Broilers fed on diet containing 6% koroch seed cake yielded the lowest dressed weight in the treatment groups. Inclusion of 2% koroch seed cake resulted in higher breast meat yield compared to any other level of koroch cake inclusion in the diet (P<0.01). However, liver and gizzard weight were increased significantly (P<0.05) for incorporation of de-oiled koroch seed cake in the diet at all levels (2%, 4% or 6%). On the basis of these results it is concluded that feeding de-oiled koroch cake had no positive effect on growth response and meat yield characteristics of broiler. Therefore, it is suggested that the koroch seed cake may contain anti-nutritional factor(s), which seemed to be associated with growth depression in broilers. Further research is warranted to alleviate the potential toxic effect of koroch seed cake on broiler performances. Res. Agric., Livest. Fish.3(2): 315-321, August 2016